Synthesis of Some Polydiactylene Esters - Al-Ajely, Mohammad S.; Qasim, Ammar A. (Science Journal of University of Zakho, 2013)
Some diacetylene ester compounds(1-13) were prepared using the well known coupling procedures. These diacetylenes monomers were polymerized by the topochenical process using UV irradiation. The resulted polymers (14-26) were found to be insoluble in all common organic solvents. The monomers were identified by IR,NMR and Mass measurements while the polymers were identified depending on their physical changes(due to insolubility ) and the identification of their oligomers by Mass and NMR measurments.